Relaxing credit constraints in emerging economies: The impact of public loans on the productivity of Brazilian manufacturers - Lage de Sousa, Filipe; Ottaviano, Gianmarco I.P. (International economics (Paris), 2018)
In emerging economies credit constraints are often perceived as one of the most important market frictions hampering firm productivity growth in manufacturing. Huge amount of public money is devoted to the removal of such constraints but its effectiveness is still subject to an intense policy debate. This paper contributes to this debate by analyzing the effects of the Brazilian Development Bank (BNDES) loans. Exploiting the unique features of a dataset on BNDES loans to Brazilian manufactures, it finds that credit constraints facing Brazilian manufacturing firms are real, in particular for firms that apply to BNDES repeatedly, and BNDES support has allowed granted firms to match the performance of similar unconstrained firms but not to outperform them. •BNDES provides loans aimed at enhancing the productivity of manufactures.•Beneficiaries are credit constrained, in particular if they apply repeatedly.•Beneficiaries perform as similar unconstrained firms at least in the short run.•Beneficiaries do not outperform similar unconstrained firms.